The Effect of Compliance Pressure, Time Budget Pressure, and Task Complexity on Audit Judgment in Public Accounting Offices, Denpasar Bali - Luh Pande Eka Setiawati; Anak Agung Sagung Istri Pramanaswari; M. Doni Permana Putra (Journal of International Conference Proceedings, 2022)
This study aims to determine the effect of compliance pressure, time budget pressure, and task complexity on audit judgment. The population in this study all auditors who work at the Public Accounting Firm (KAP) in the Bali area contained in the 2022 Directory and the sample used is 74 respondents. Based on the results of the study, it can be seen that: (1) Obedience pressure has no significant negative effect on audit judgment, where the regression coefficient is -0.006 and sig 0.962, (2) Time budget pressure has a significant negative effect on audit judgment where the regression coefficient is -0.180 and sig 0.023, and (3) task complexity has a significant positive effect on audit judgment where the regression coefficient is -0.108 and sig 0.047. Suggestions that can be given by researchers are further researchers, so that they can examine and examine more deeply other factors not examined in this study that can affect audit judgment.Â Keywords: Audit judgment, Compliance pressure, Task complexity, Time budget pressure.